Upaya Meningkatkan Hasil Belajar IPS Dengan Metode Diskusi Menggunakan Media Gambar Di Kelas VII-3 SMP Negeri 2 Palangka Raya - Salya Marshanda; Santi Endriani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to determine the learning activities of students and increase learning outcomes of social studies students. The method used in this study was to use the Classroom Action Research (CAR) design. The subjects needed in this study were students of class VII-3 of SMP Negeri 2 Palangka Raya, amounting to 29 students, for data collection techniques used observation and tests. While in this study using qualitative and quantitative data analysis. The results of the study show that: (1) Student learning activities are good. This is evidenced by the increase in the average score of learning activities of students in the first cycle obtaining an average score of 3.86 with the criteria of Good. (2) There is an increase in learning outcomes as evidenced by an increase in classical completeness from pre-action (pre-test), learning outcomes of students get an average score of 36.89 with completeness of 0% or no students complete or score ≤75 and post-test cycle I learning outcomes students get an average value of 80.51 with completeness 96.55% or get a value of ≥75.